2021
DOI: 10.20944/preprints202108.0350.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Nociceptive Role of the Thoracolumbar Fascia: A Scope Review Involving in Vivo and Ex Vivo Studies

Abstract: Nociceptive innervation of the thoracolumbar fascia (TLF) has been investigated over decades, however these studies have not been compiled or collectively appraised. The purpose of this scoping review was to assess current knowledge regarding nociceptive innervation of the TLF to better inform future mechanistic and clinical TLF research targeting low back pain (LBP) treatment. PubMed, ScienceDirect, Cochrane and Embase databases were searched in January 2021 using relevant descriptors encompassing fascia and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(151 reference statements)
1
2
0
Order By: Relevance
“…[16] and Mense [5] found a signi cantly increased density of substance P-positive bers in in amed rat TLF. These bers are generally considered to be nociceptive [50] and could lead to higher pain sensitivity, which is also consistent with the strong correlation of TLFM and ODQ-D found at baseline.…”
Section: Discussionsupporting
confidence: 82%
“…[16] and Mense [5] found a signi cantly increased density of substance P-positive bers in in amed rat TLF. These bers are generally considered to be nociceptive [50] and could lead to higher pain sensitivity, which is also consistent with the strong correlation of TLFM and ODQ-D found at baseline.…”
Section: Discussionsupporting
confidence: 82%
“…Given that lumbodorsal fascia is innervated and could be a potential source of low back pain [6][7][8][9][10][11][12], it is intriguing to understand how lumbodorsal fasciitis will effect on the induction and relief of back pain associated with OVCF. Here we showed that patients with lumbodorsal fasciitis more often complained longer duration of back pain before hospitalization, suggesting a possible contribution of the fasciaoriginated pain to distract patients from the fracture-induced pain.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, an edema signal could also be detected subcutaneously dorsal to the thoracolumbar fascia, suggesting a comorbidity of lumbodorsal fasciitis in the OVCF [3][4][5]. While the epidemiology and pathogenesis of lumbodorsal fasciitis remain elusive, evidence accumulates that the lumbodorsal fascia is innervated with terminal nerves and could be a potential source of acute or chronic low back pain [6][7][8][9][10][11][12]. It has been increasingly recognized that the presence of thoracolumbar fascia edema potentially contributes to the residual back pain after percutaneous kyphoplasty [15][16].…”
Section: Introductionmentioning
confidence: 99%